MANAGEMENT OF INDICATOR-INSTRUMENTAL EVALUATION OF EFFICIENCY OF PROFESSIONAL AND TECHNICAL EDUCATIONAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2022)
It is a question deals with the need of introducing a system indicators PTUZ effectiveness of active with a view to studying indicators of qualified workers in training. determining the conformity between mand for labour and proposals, improving the educational services market flexibility, its openness to the pedagogical introduction of new technologies.
Keywords: monitoring; the work; indicator